Aboagora - Between Arts and Sciences - Illman, Ruth (Approaching Religion, 2011)
The editorial note presents the journal and the current issue. The purpose of this e-journal is to contribute to the plurality of voices in the academic discussion on religion. Approaching Religion aims at offering an accessible, open and explorative forum for scholarly debate on timely issues and concepts related to the study of religion and culture. In order to fulfil the goals of availability and visibility, we have created our journal as an online, open access publication, supported by the internationally compatible Open Journal Systems (OJS) platform. Approaching Religion is primarily a publication channel for articles presented at seminars and conferences arranged by the Donner Institute for Research in Religious and Cultural History in Åbo, Finland. The journal addresses an international readership and our aim is to present articles of highest academic standard that approach the field of religion from a broad, theoretically and methodologically diverse perspective.